A Luminescent Dinuclear EuIII/TbIII Complex with LMCT Band as a Single‐Molecular Thermosensor. Issue 8 (16th January 2018) - Yanagisawa, Kei; Kitagawa, Yuichi; Nakanishi, Takayuki; Seki, Tomohiro; Fushimi, Koji; Ito, Hajime; Hasegawa, Yasuchika
Abstract: Temperature‐dependent luminescence of a dinuclear Eu III /Tb III complex with a seven‐coordinate structure is demonstrated. The dinuclear complex is composed of two lanthanide ions, six tetramethylheptanedionate ligands, and a bidentate phosphine oxide linker ligand. The dinuclear structure of the complex was characterized by single‐crystal XRD. Intrinsic 4f–4f emission quantum yields of the dinuclear Eu III and Tb III complexes were 66 and 61 %, respectively. The luminescence color of the dinuclear Eu III /Tb III complex changed from red to green with increasing temperature. The thermosensing range based on the ratio of luminescence intensity ( A Eu / A Tb ) was 100–450 K. The temperature‐dependent luminescence is due to the presence of a ligand‐to‐metal charge‐transfer state. Abstract : Temperature‐dependent luminescence of a dinuclear Eu III /Tb III complex was demonstrated. The unexpected luminescence color change from red to green with increasing temperature (see figure) was exploited for thermosensing in the temperature range 100–450 K. The temperature‐dependent luminescence properties are due to the presence of a ligand‐to‐metal charge‐transfer state.